Solidarity: A Structural Principle of International Law - Wolfrum, Rüdiger (Springer-Verlag Berlin Heidelberg, 2010)
Presents a discussion on whether the concept of solidarity functions as a structural principle of international law and to what extent it has become a full-fledged legal principle
"The symposium ... was held at the Max Planck Institute for Comparative Public Law and International Law in Heidelberg on 29 October 2008"--Acknowledgments
Includes bibliographical references
Keywords: Konferenzschrift -- 2008 -- Heidelberg; Internationales Recht; Solidarität